Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the vertex of the quadratic function [tex]\( y = -(x-1)(x+3) \)[/tex], we follow these steps:
1. Expand the given function:
[tex]\[ y = -(x-1)(x+3) \][/tex]
First, let's expand the expression inside the parentheses:
[tex]\[ (x-1)(x+3) = x^2 + 3x - x - 3 = x^2 + 2x - 3 \][/tex]
Now, multiplying by [tex]\(-1\)[/tex]:
[tex]\[ y = -(x^2 + 2x - 3) = -x^2 - 2x + 3 \][/tex]
So, we have the function in standard form:
[tex]\[ y = -x^2 - 2x + 3 \][/tex]
2. Identify the coefficients:
In the standard form [tex]\( y = ax^2 + bx + c \)[/tex], the coefficients are:
[tex]\[ a = -1, \quad b = -2, \quad c = 3 \][/tex]
3. Find the vertex:
The vertex of a parabola in the form [tex]\( y = ax^2 + bx + c \)[/tex] is given by the coordinates [tex]\((h, k)\)[/tex], where:
[tex]\[ h = -\frac{b}{2a} \][/tex]
Plugging in the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ h = -\frac{-2}{2(-1)} = \frac{2}{-2} = -1 \][/tex]
To find the y-coordinate [tex]\(k\)[/tex], substitute [tex]\(h = -1\)[/tex] back into the function:
[tex]\[ k = a(-1)^2 + b(-1) + c \][/tex]
[tex]\[ k = -1(-1)^2 - 2(-1) + 3 = -1(1) + 2 + 3 = -1 + 2 + 3 = 4 \][/tex]
Thus, the vertex of the function is:
[tex]\[ (-1, 4) \][/tex]
4. Conclusion:
The vertex of the graph of the function [tex]\( y = -(x-1)(x+3) \)[/tex] is [tex]\(\boxed{(-1, 4)}\)[/tex].
1. Expand the given function:
[tex]\[ y = -(x-1)(x+3) \][/tex]
First, let's expand the expression inside the parentheses:
[tex]\[ (x-1)(x+3) = x^2 + 3x - x - 3 = x^2 + 2x - 3 \][/tex]
Now, multiplying by [tex]\(-1\)[/tex]:
[tex]\[ y = -(x^2 + 2x - 3) = -x^2 - 2x + 3 \][/tex]
So, we have the function in standard form:
[tex]\[ y = -x^2 - 2x + 3 \][/tex]
2. Identify the coefficients:
In the standard form [tex]\( y = ax^2 + bx + c \)[/tex], the coefficients are:
[tex]\[ a = -1, \quad b = -2, \quad c = 3 \][/tex]
3. Find the vertex:
The vertex of a parabola in the form [tex]\( y = ax^2 + bx + c \)[/tex] is given by the coordinates [tex]\((h, k)\)[/tex], where:
[tex]\[ h = -\frac{b}{2a} \][/tex]
Plugging in the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
[tex]\[ h = -\frac{-2}{2(-1)} = \frac{2}{-2} = -1 \][/tex]
To find the y-coordinate [tex]\(k\)[/tex], substitute [tex]\(h = -1\)[/tex] back into the function:
[tex]\[ k = a(-1)^2 + b(-1) + c \][/tex]
[tex]\[ k = -1(-1)^2 - 2(-1) + 3 = -1(1) + 2 + 3 = -1 + 2 + 3 = 4 \][/tex]
Thus, the vertex of the function is:
[tex]\[ (-1, 4) \][/tex]
4. Conclusion:
The vertex of the graph of the function [tex]\( y = -(x-1)(x+3) \)[/tex] is [tex]\(\boxed{(-1, 4)}\)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.